Un Marco de Trabajo para el Desarrollo de Software Web Seguro con Metodologías Ágiles - Valderrama Herrera, Gilmer Glicerio (2024)
Software development using the agile approach with SCRUM presents itself as an alternative to traditional methodologies, offering incremental, iterative features and continuous code delivery that ensure a product adaptable to changes. However, this approach faces challenges in terms of secure development, as threats and vulnerabilities may not be adequately addressed due to tight deadlines and frequent changes in requirements. In this context, a framework for secure web software development using Agile Methodologies (SCRUM) is proposed. Based on the literature, eight security activities have been selected for this purpose and integrated into the development process, considering their level of agility and cost-benefit. The validity of this proposal was confirmed through an instrument that gathered the opinions of 45 experts in the software development industry in Peru.